An Intersensory Interaction Account of Priming Effects—and Their Absence. (January 2014) - Klatzky, Roberta L.; Creswell, J. David
Psychological researchers have found that exposures to stimuli (primes) can subsequently influence people's behavior by pathways that would seem to be quite remote. For example, people exposed to words associated with older adults may walk more slowly. Recently priming studies, particularly those showing dramatic effects on social behavior, have been under scrutiny because of the unreliability of empirical results. In this article, we shed light on the issue by describing a general model of intersensory interaction, in which two or more sources of information provide an estimate or "bid" on a property of the world, with the perceptual outcome being a weighted combination of the bids. When it is extended by adding bids that stem from memory or inference, the model identifies systematic factors that might undermine priming, including random variation in estimates, contextual influences on memory retrieval and inference, competition among information sources, and cognitive control. These factors are not only explanatory but are predictive of when priming effects can be expected. Our hope is that by promoting the understanding of underlying processes that may explain how primes can influence behavior, the bidding model and the general approach that it represents offer novel insights into the hotly debated area of priming research.